Tidal turbine modelling from the perspective of design and operation - Corsar, Michael (Cranfield University, 2016)
The aim of this thesis is to study the effects of turbulent flow on a fixed pitch tidal current turbine from the perspective of turbine design and operation. A prototype turbine, Deltastream as it is known, is being developed by Tidal Energy Ltd for deployment in Ramsey Sound, Wales. It is well known that turbulence plays an important role in the fatigue life of marine turbines. Field measurements of tidal flow at the turbine site were analysed to establish the velocity spectra and turbulence intensity. This revealed a wide range of anisotropic turbulence which is dependent upon the tidal direction with intensities ranging from 5-20%. A numerical turbine model based on momentum theory was constructed in a time marching formulation that accounts for the effects of dynamic inflow and rotationally augmented airfoil stall delay properties. The turbine rotor design allows for load alleviation by regulation of the turbine tip speed ratio. At flow velocities above the rated velocity the tip speed ratio can be increased to reduce turbine loads. The model has been combined with a novel rotor speed control algorithm that estimates unsteady turbine inflow velocity from turbine loading without the requirement for external sensing of flow speed. When the turbine is subjected to three dimensional turbulent inflow the rotor speed controller has been shown to significantly reduce the fatigue effect of unsteady, turbulent flow. The turbine blade design has been developed using the model established. Experimental validation studies were carried out at 1/16th scale in turbulent conditions. Studies using the model have; identified the relationship between turbulence intensity and turbine fatigue load, established a controller schedule to significantly reduce fatigue loading and determined the blading fatigue life in realistic turbulent flows.
Keywords: turbulence; dynamic inflow; fixed patch turbine